Application of the Analytical Hierarchy Process Model in the Selection of Audit Software at the Southeast Sulawesi Regional Inspectorate - Hajar, Khaerunnisa Ibnu; Arjuna, Bucek Jalu Prasetyo; Hajar, Nuzul Ibnu (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the criteria and sub-criteria that are prioritised by auditors in determining the audit software used in the Southeast Sulawesi Regional Inspectorate. The researchers used a qualitative approach with the Multi-Criteria Decision Making (MCDM) method using the Analytical Hierarchy Processes (AHP) analysis tool. The research sample consisted of all auditors at the Southeast Sulawesi Regional Inspectorate. The results of data analysis at the Southeast Sulawesi Regional Inspectorate showed that technical functions were the main priority for auditors in selecting audit software, while vendor support criteria were low priority criteria. Based on the questionnaire results, the software used by auditors was Microsoft Excel, while ACL was the least used application with the lowest percentage. The Government Internal Supervisory Agency (APIP) currently uses Computer-Assisted Audit Techniques (TABK). Therefore, the selection of audit applications can be determined through the Analytical Hierarchy Process (AHP) approach to select audit applications in accordance with the needs of the Southeast Sulawesi Province APIP. The results of this study will later be added to the discussion of theory and literature on the application of AHP in government agencies and institutions at the regional level in decision-making on the use of computer-based government information systems. This study is limited to the sub-criteria of audit software and the main criteria for the use of audit software and statistical criteria.